Towards the development of a electronic voting system prototype for the Costa Rican context - Schmidt-Peralta, Jeff (2016)
Digital communication and information technologies have been incorporated in our daily activities in a transversal way, and those of public interest have been studied particularly carefully. In electoral processes, because of their complexity and particular requirements, the adoption of digital technology have been done with suspiciousness, but without closing doors because of the encouraging opportunities to improve the process. In this article the aim is to present the process of developing a prototype for electronic voting adapted to the particularities of the Costa Rican electoral process. The implemented solution uses free licensed software, which makes it fully auditable. The design and construction of the prototype are results of research project “Electronic Vote”, adscribed in the Costa Rica Institute of Technology (TEC).